TIME SERIES ANALYSIS OF THE AFOEV OBSERVATIONS OF SYMBIOTIC STARS UV AUR, TX CVN AND V 1329 CYG - Chinarova, L. L.; Andronov, I. L.; Schweitzer, E. (Одеські астрономічні публікації, 2017)
One frequency sine approximations allowed to obtain the following best fit parameters: periods P = 389.23 ± 0.47d, 3779±73d, 958.7±1.2d mean brightness a = 9.23±0.02m, 9.73±0.01m, 13.26 ±0.07m. semi-amplitudes r = 0.92 ± 0.026m, 0.02 ± 0.007m, 0.49±0.10m and epochs for mean maxima Tm = 2446551.4± 1.8, 7014±21, 5345± 3d for UV Aur, TX CVn and V 1329 Cyg, respectively. Extreme values and cycle lengths vary with time, their characteristics are tabulated.